Altered bone development with impaired cartilage formation precedes neuromuscular symptoms in spinal muscular atrophy. (9th July 2020) - Hensel, Niko; Brickwedde, Hermann; Tsaknakis, Konstantinos; Grages, Antonia; Braunschweig, Lena; Lüders, Katja A; Lorenz, Heiko M; Lippross, Sebastian; Walter, Lisa M; Tavassol, Frank; Lienenklaus, Stefan; Neunaber, Claudia; et al.
Abstract: Spinal muscular atrophy (SMA) is a fatal neurodegenerative disease of newborns and children caused by mutations or deletions of the survival of motoneuron gene 1 resulting in low levels of the SMN protein. While neuromuscular degeneration is the cardinal symptom of the disease, the reduction of the ubiquitously expressed SMN additionally elicits non-motoneuron symptoms. Impaired bone development is a key feature of SMA, but it is yet unknown whether this is an indirect functional consequence of muscle weakness or caused by bone-intrinsic mechanisms. Therefore, we radiologically examined SMA patients in a prospective, non-randomized cohort study characterizing bone size and bone mineral density (BMD) and performed equivalent measurements in pre-symptomatic SMA mice. BMD as well as lumbar vertebral body size were significantly reduced in SMA patients. This growth defect but not BMD reduction was confirmed in SMA mice by μCT before the onset of neuromuscular symptoms indicating that it is at least partially independent of neuromuscular degeneration. Interestingly, the number of chondroblasts in the hypertrophic zone of the growth plate was significantly reduced. This was underlined by RNAseq and expression data from developing SMA mice vertebral bodies, which revealed molecular changes related to cell division and cartilage remodeling. Together, these findings suggest a bone intrinsic defect in SMA. This phenotype may not be rescued by novel drugs that enhance SMN levels in the central nervous system only.